The effect of group work strategy in English teaching and learning in SMP Bandar Lampung - Supriyadi, Deddy; Sholihah, Lilis; Shafwati, Dian (Universitas Lampung, 2022)
This research aims to analyze the effect of group learning strategies in teaching and learning English at the stage of junior high schools in Bandar Lampung. Moreover, this study used a descriptive qualitative research. Observation, open-ended questionnaires, and interviews were used in this study. The result of this study showed that the group work strategy had significant effect towards English learning outcomes. In addition, some teachers and students approved that the group work strategy is an active learning strategy. It was proven by teachers’ answers on open-ended questionnaires. In sum, it can be inferred that group work strategy can be used to make an active learning and improve students’ outcomes in learning English. Although in pandemic situation, group work strategy can be applied by using some application which can support teaching and learning English. Keywords: learning strategy, group work